Find the value of x in the equation below. 9(x-5)=4x-5
9(x-5)=4x-5 9x - 45 = 4x - 5 9x - 4x = - 5 + 45 5x = 40 x = 8
g
Updated 4/9/2014 6:29:56 PM
Rating
3
9(x-5)=4x-5
9x - 45 = 4x - 5
9x - 4x = - 5 + 45
5x = 40
x = 8
Confirmed by jeifunk [4/9/2014 6:34:34 PM]

Carlos has \$3.35 in dimes and quarters. If he has a total of 23 coins, how many dimes does he have? a 9 b 11 c 16 d 18
Updated 4/9/2014 8:13:29 PM
Let x be the number of dimes he has and y be the number of quarters,
we were given:
x + y = 23
10x + 25y = 335
Solve the equation we get x = 16
Carlos has 16 dimes.
Confirmed by jeifunk [4/9/2014 8:27:53 PM]
Solve each system of equations. If possible, write your answer as an ordered pair. y = -3x + 2 y = 4x - 5
Weegy: 4x + 12 = -3x - 6 + 4x, 4x + 12 = x - 6, 12 + 6 = x - 4x, 18 = -3x or -3x = 18, x = -6 (More)
Updated 4/9/2014 8:06:24 PM
y = -3x + 2
y = 4x - 5
replace y in the first equation we get:
4x - 5 = -3x + 2
4x + 3x = 2 + 5
7x = 7
x = 1
y = 4(1) - 5 = -1
The solution for the system of equations y = -3x + 2 y = 4x - 5 is (1, -1)
Confirmed by jeifunk [4/9/2014 8:06:50 PM]
Solve each system of equations. If possible, write your answer as an ordered pair. y = 5x - 3 y = 2x + 6
Updated 4/9/2014 8:04:27 PM
y = 5x - 3
y = 2x + 6
replace y in the first equation we get:
2x + 6 = 5x - 3
2x - 5x = -3 - 6
-3x = -9
x = 3
y = 5(3) - 3 = 15 - 3 = 12
The solution for the system of equations y = 5x - 3 y = 2x + 6 is (3, 12)
Confirmed by jeifunk [4/9/2014 8:08:11 PM]
Solve each system of equations. If possible, write your answer as an ordered pair. x + y = 8 x + 3y = 14
Weegy: 1 x - 3 y = - 6 ? y = x 3 + 2 (More)
Updated 4/9/2014 7:52:39 PM
x + y = 8
x + 3y = 14
the first equation - the second equation: 2y = 6
solve the equation: y = 3
x + 3 = 8, x = 5
The solution for the system of equations x + y = 8, x + 3y = 14 is (5, 3)
Confirmed by jeifunk [4/9/2014 8:06:37 PM]
Solve each system of equations. If possible, write your answer as an ordered pair. y = -2x + 6 y = 3x - 9
Weegy: x = 2.5 (More)
Updated 4/9/2014 7:55:11 PM
y = -2x + 6
y = 3x - 9
Replace y in the first equation:
3x - 9 = -2x + 6
5x = 15,
x = 3
y = -2(3) + 6 = 0
The solution for the system of equations y = -2x + 6 y = 3x - 9 is (3, 0)
Confirmed by jeifunk [4/9/2014 8:02:39 PM]
32,251,442
*
Get answers from Weegy and a team of really smart live experts.
S
L
P
L
P
P
Points 1341 [Total 9441] Ratings 0 Comments 1341 Invitations 0 Online
S
L
P
R
P
R
L
P
P
C
R
P
R
L
P
R
P
R
Points 1332 [Total 15087] Ratings 6 Comments 1252 Invitations 2 Online
S
L
Points 1152 [Total 1521] Ratings 0 Comments 1152 Invitations 0 Offline
S
L
P
1
L
Points 1068 [Total 5351] Ratings 9 Comments 978 Invitations 0 Offline
S
L
P
P
P
1
P
L
Points 600 [Total 8051] Ratings 14 Comments 460 Invitations 0 Offline
S
L
L
1
Points 581 [Total 6497] Ratings 6 Comments 521 Invitations 0 Offline
S
L
Points 451 [Total 482] Ratings 0 Comments 1 Invitations 45 Offline
S
L
1
Points 286 [Total 4290] Ratings 9 Comments 196 Invitations 0 Offline
S
L
Points 281 [Total 2815] Ratings 3 Comments 251 Invitations 0 Offline
S
L
Points 229 [Total 314] Ratings 1 Comments 219 Invitations 0 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.